Effect of Queue Management System on Patient Satisfaction in Emergency Department; a Randomized Controlled Trial - Bidari, Ali; Jafarnejad, Shabahang; Alaei Faradonbeh, Nazanin (Archives of Academic Emergency Medicine, 2021)
Introduction: Patients’ experience in hospitals affects their satisfaction. The purpose of the present study was to assess the effect of applying a queue management system on patient satisfaction in emergency department waiting rooms. Methods: The present prospective randomized single-blinded interventional study was performed from July to August 2020 and involved 236 patients that were divided into one intervention group and one control group, each consisting of 118 patients. The mentioned patients’ perception of the waiting time and satisfaction before being visited by an emergency medicine doctor was evaluated with and without applying the queue management system. Results: The mean actual waiting time (15.5 ± 7.5 minutes) as well as the mean perceived waiting time (11.9 ± 7.4 minutes) for the intervention group were significantly lower than those of the control group with the values of 27.03 ± 8.5 and 32.8 ± 8.7 minutes, respectively (p < 0.001). The mean perceived waiting time was significantly less than the mean actual waiting time (11.9 min vs 15.5 minutes) for the intervention group (p <0.001); however, the mean perceived waiting time was significantly higher than the mean actual waiting time (32.8 vs 27.03 minutes) for the control group (p < 0.001). The level of satisfaction in the intervention group was significantly higher than that of the control group (p <0.001). There was an inverse relationship between the actual waiting time (Intervention group: r=-0.463; Control group: r= -0.567) and the perceived waiting time (Intervention group: r= -0.439; Control group: r= -0.568) with the satisfaction level in both groups (p < 0.001). Conclusion: It can be proposed that the application of a queue management system in the emergency department waiting rooms can reduce the actual and perceived waiting times and increase the patient satisfaction.